2009
DOI: 10.1007/s10584-009-9666-3
|View full text |Cite
|
Sign up to set email alerts
|

Do we need to include soil evolution module in models for prediction of future climate change?

Abstract: Climate change induce increases in precipitation in Northern Europe that may in turn affect soil evolution by increasing the amounts of water flowing through soils. However, there is a general lack of consideration of the impact of climate change on soil evolution. We propose here to use agricultural soil drainage-that also increases the amount of water flowing through soils-as an analogy to climate change. We thus studied the impact of 16 years of agricultural drainage in one cropped plot of the most common t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Despite the importance of the hydrological processes in this context, their consideration within soil-landscape evolution models (SLEMs) is still insufficient (Samouëlian et al, 2012). Landscape evolution modeling is an important tool to better understand landscape formation but also to assess how landscapes are affected by global climate change (Montagne and Cornu, 2010) or anthropogenic interventions (Cui et al, 2021) such as land use change and hydrologic alterations (Newman et al, 2017). In particular, the evolution of vertical and horizontal subsurface flow paths -including the occurrence of preferential flow paths -are currently omitted in SLEMs (van der Meij et al, 2018), which can lead to incorrectly modeled transport and relocation processes (Sauer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of the hydrological processes in this context, their consideration within soil-landscape evolution models (SLEMs) is still insufficient (Samouëlian et al, 2012). Landscape evolution modeling is an important tool to better understand landscape formation but also to assess how landscapes are affected by global climate change (Montagne and Cornu, 2010) or anthropogenic interventions (Cui et al, 2021) such as land use change and hydrologic alterations (Newman et al, 2017). In particular, the evolution of vertical and horizontal subsurface flow paths -including the occurrence of preferential flow paths -are currently omitted in SLEMs (van der Meij et al, 2018), which can lead to incorrectly modeled transport and relocation processes (Sauer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Mass flux calculations indicated that Cu mass flux (m Cu flux ) at position 0.6 m was, on average, three times higher than at positions 2.1 and 4.0 m (43.8 and 15.3 mg cm − 2 , respectively). This loss of Cu from the E & Bt horizon at position 0.6 m is linked with substantial loss of Fe and clay at positions 0.6 m and 1.1 m, (6.5 and 2.3 kg m − 2 Fe and 75.8 and 25.6 kg m − 2 clay, respectively; Montagne and Cornu, 2010). The loss has been explained by strongly enhanced eluviation caused by drainage-induced higher water fluxes, and is most pronounced in the upper part of the E & Bt horizon at position 0.6 m (Montagne and Cornu, 2010).…”
Section: Response Of Cu Concentrations and δ 65 Cu Values To Drainagementioning
confidence: 97%
“…This loss of Cu from the E & Bt horizon at position 0.6 m is linked with substantial loss of Fe and clay at positions 0.6 m and 1.1 m, (6.5 and 2.3 kg m − 2 Fe and 75.8 and 25.6 kg m − 2 clay, respectively; Montagne and Cornu, 2010). The loss has been explained by strongly enhanced eluviation caused by drainage-induced higher water fluxes, and is most pronounced in the upper part of the E & Bt horizon at position 0.6 m (Montagne and Cornu, 2010). These findings agree with the close correlation between the clay and the Cu concentrations (Fig.…”
Section: Response Of Cu Concentrations and δ 65 Cu Values To Drainagementioning
confidence: 97%
“…Clay translocation has been considered as occurring mostly under boreal conditions and consequently as a fossil process in temperate conditions [50]. Recent research, however, clearly demonstrated that this process is still active nowadays in temperate climate [32,39] and that its intensity is particularly sensitive to anthropic or climatic global changes [29,33]. As increasing intensity of clay translocation may correspond to increasing risks of erosion and compaction in surface soil horizons, to increasing transfer of soil contaminants associated with eluviated soil particles but also to increasing long-term C sequestration in subsoil horizons [48], it seems thus necessary to better understand its mechanisms notably at the microscopic scale.…”
Section: Introductionmentioning
confidence: 99%